Об одной модели разграничения доступа к ресурсам информационной системы «Население и миграция» с использованием сетей Петри - Абдуллаева, Ф.Д. (Проблемы управления и информатики, 2008)
Запропоновано модель авторизації, яка дозволяє користувачу отримати доступ до потрібних ресурсів інформаційної системи «Населення та міграція». Для цього застосовується механізм забезпечення і відміни привілеїв користувачу. Модель авторизації реалізовує функції ролевого контролю доступу користувача за допомогою кольорових мереж Петрі. A model of the authorization that allows users to gain access to required resources of information system «Population and migration» is offered. For this purpose the mechanism of granting and revoking privileges to users is applied. The model of authorization implements the functions of the role based access control and for this purpose is given model of the authorization process by means of colored Petri nets.